Guarding the Gates: The Canadian Labour Movement and Immigration, 1872-1934 - Goutor, David (UBC Press, 2007)
From the 1870s until the Great Depression, immigration was often the question of the hour in Canada. Politicians, the media, and an array of interest groups viewed it as essential to nation building, developing the economy, and shaping Canada’s social and cultural character. One of the groups most determined to influence public debate and government policy on the issue was organized labour, and unionists were often relentless critics of immigrant recruitment. Guarding the Gates is the first detailed study of Canadian labour leaders’ approach to immigration, a key battleground in struggles between different political factions within the labour movement. --Publisher's description
Keywords: Emigration and immigration; Employment; Government policy; History; Immigrants; Labor Unions; Race discrimination